Mustafa's Jumper - Rumble, Coral; Cooke, Charlotte (London, UK : Wacky Bee Books, 2019)
Milo isn't extra clever, or extra naughty, or extra anything. And he doesn't get chosen to do things very often. But when a mysterious new boy, who can't speak any English, joins his class, Milo's curiosity gets the better of him. As he becomes closer to Mustafa, he discovers that the language of friendship is more important than speaking the same words.
Keywords: Refugees -- Children's fiction; Friendship -- Children's fiction